Теплові втрати трубопроводами мікрорайонної опалювальної мережі в умовах зміни теплового навантаження будівель - Алексахін, Олександр Олексійович; Бобловський, О. В.; Єна, Світлана Василівна (НТУ "ХПІ", 2015)
Розглянуто вплив додаткової теплоізоляції будівель на тепловтрати трубопроводами мікрорайонної опалювальної мережі. Проаналізовано зміну теплових втрат в залежності від черговості утеплення будівель мікрорайону. Показано, що найменші тепловтрати характерні для варіанту утеплення найбільш віддалених від центрального теплового пункту будівель. Дани рекомендації, що при виборі варіанта утеплення будинків однією із гілок сеті треба враховувати, що при утеплені споруд, приєднаних до гілки більшої довжини, сумарні втрати теплоти опалювальною сіткою менші.

Consideration is given to the influence produced by the additional heat insulation of buildings on thermal losses in the pipelines of microdistrict heating network. A change in thermal losses depending on the priority of the heat insulation of microdistrict buildings has been analyzed. It has been shown that a decrease in the estimated heat load of the buildings for which the heat insulation is provided results in a decrease of heat losses in microdistrict network pipelines. It has been established that from the point of view of a decrease in thermal losses in network pipelines it is reasonable to provide with the heat insulation first the buildings that are more remote from the central thermal station for the efficient step-by-step heat insulation work over several seasons. While selecting the option of the heat insulation for the buildings of one of the network branches it is recommended to take into consideration the fact that total heat losses in the heating network will be lower if the heat insulation is provided for the buildings connected to a longer branch.
Thermal losses in the pipelines of microdistrict heating network under conditions of changed thermal load in buildings
Keywords: житлово-комунальний сектор; централізоване теплопостачання; теплоізоляція будівель; district heating; heat losses; heat insulation of buildings